A proposal of all-wavelength optical amplifiers - Surasak Pipatsart; Ura Dunmeekaew; Nithiroth Pornsuwancharoen; Preecha P. Yupapin (My University, 2009)
We have shown the interesting results of the optical signal amplifications using a Gaussian pulse propagating within a nonlinear microring resonator system. Several Gaussian pulses with different center wavelengths, for instance, 400–1500 nm are investigated using the designed system. Results have shown that the optical signal amplification using the nonlinear ring resonator is plausible. By using the input power of 2 W, the optical output of 15 W is achieved. The interesting aspect is that all Gaussian input wavelengths can be amplified which can be useful for other wavelengths in future communication.
Keywords: SIGNAL (programming language); Photonic and Optical Devices